Utilization of Social Media and Price Setting for MSME Product Purchase Decisions during the COVID-19 Pandemic in Stabat District - Nel Arianty (AIBPM Publisher, 2022)
The impact of the COVID-19 pandemic has made price competition for MSME products Es Gak Beres and KZL Durian Kebabs affect consumer purchasing decisions in the Stabat Kwala Begumit District. Consumer purchasing decisions for an item are strongly influenced by the price, product, service, location of the company/store. Social media is an internet-based application service that allows consumers to share opinions, thoughts, views and experiences. Price is the money (plus some products) required to obtain some combination of products and services. Partially it can be concluded that there is a significant influence between Social Media on Purchase Decisions on Es Gak Beres and Kebab Durian MSME products in Binjai Kwala Begumit District during the Covid-19 Pandemic. Partially it can be concluded that there is no significant effect between price and purchasing decisions on Es Gak Beres and Kebab Durian MSME products in Stabat Kwala Begu-mit District during the Covid-19 Pandemic Period. Simultaneously, it can be concluded that there is an influence of Social Media and Price on the Purchase Decision of MSME Products Ice Gak Beres and Durian Kebabs in Stabat Kwala Begumit District during the Covid-19 Pandemic Period. Keywords: Social Media, Price, MSME, Purchase Decision and Covid-19